Color stability of maxillofacial silicone with nanoparticle pigment and opacifier submitted to disinfection and artificial aging - Haddad, Marcela Filie [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Moreno, Amalia [UNESP]; D'almeida, Nuno Filipe; Pesqueira, Aldieris Alves [UNESP] (Spie-soc Photo-optical Instrumentation Engineers, 2011)
The purpose of this study was to evaluate the color stability of a maxillofacial elastomer with the addition of a nanoparticle pigment and/or an opacifier submitted to chemical disinfection and artificial aging. Specimens were divided into four groups (n = 30): group I: silicone without pigment or opacifier, group II: ceramic powder pigment, group III: Barium sulfate (BaSO(4)) opacifier, and group IV: ceramic powder and BaSO(4) opacifier. Specimens of each group (n = 10) were disinfected with effervescent tablets, neutral soap, or 4% chlorhexidine gluconate. Disinfection was done three times a week during two months. Afterward, specimens were submitted to different periods of artificial aging. Color evaluation was initially done, after 60 days (disinfection period) and after 252, 504, and 1008 h of artificial aging with aid of a reflection spectrophotometer. Data were analyzed by three-way ANOVA and Tukey test (alpha = 0.05). The isolated factor disinfection did not statistically influence the values of color stability among groups. The association between pigment and BaSO(4) opacifier (GIV) was more stable in relationship to color change (Delta E). All values of Delta E obtained, independent of the disinfectant and the period of artificial aging, were considered acceptable in agreement with the norms presented in literature. (C) 2011 Society of Photo-Optical Instrumentation Engineers (SPIE). [DOI: 10.1117/1.3625401]
Keywords: spectrophotometer; elastomers; nanoparticle; disinfection; color stability; artificial aging